THE POTENTIAL OF INNOVATION AMBIDEXTERITY: THE ROLE OF SOCIAL MEDIA AND PHILANTHROPY IN ENHANCING THE SUSTAINABILITY PERFORMANCE OF MSME IN KENDAL REGENCY - Nurhidayah, Siti Abdillah; Pujiastuti, Arum; Ridhasyah, Rizki (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This research examines the impact of exploratory (SR) and exploitative (ST) innovation strategies on the sustainability performance (KK) of MSMEs in Kendal Regency within the Resource-Based View (RBV) Theory. It also explores the moderating roles of social media (MS) and philanthropy (FL). A total of 414 MSME owners or managers were randomly sampled from businesses actively using social media and engaging in philanthropy. Data were collected through questionnaires using validated constructs measured on a five-point Likert scale. Partial Least Squares Structural Equation Modeling (PLS-SEM) analyzed the data. The findings reveal that both SR and ST positively influence KK. MS strengthens the SR-KK relationship but does not moderate the ST-KK link. FL significantly enhances the effects of both SR and ST on KK. These results highlight the importance of balancing innovation strategies for sustainable performance and the complementary roles of social media and philanthropy. This study is the first to apply SEM to examine these interactions among Indonesian MSMEs. JEL: O310, O350, M140.